Fitted curve paramaters for the efficiency of a coaxial HPGe detector - Supian Samat, (Universiti Kebangsaan Malaysia, 1996)
Using Ngraph software, the parameters of various functions were determined by least squares analysis of fits to experimental efficiencies, εf of a coaxial HPGe detector for gamma rays in the energy range 59 keV to 1836 keV. When these parameters had been determined, their reliability was tested by the calculated goodness-of-fit parameter χ2cal It is shown that the function, where n = 3, gives satisfactory results.